Factors Influencing The Business Performance of SMES Convections in Kudus - Fauni, Arini Mayang; Rusdarti, Rusdarti; Wahyudin, Agus (Universitas Negeri Semarang, 2017)
Business performance can be viewed as a concept used to measure the success extent of business management influenced by entrepreneurship orientation, market orientation, business innovation, and competitive advantage. The objective of the research is to analyze and describe the influences among the tested variables directly and indirectly. The research methods used quantitative methods with path analysis. The subjects of the study are SMEs Convection in Kudus Regency.The results of the study (1) There is positive significant influence of entrepreneurship orientation to business performance directly and indirectly through competitive advantage (2) There is positive significant influence of market orientation to business performance directly and indirectly through competitive advantage (3) There is positive significant influence of business innovation on business performance directly and indirectly through competitive advantage (4) There is positive significant influence of competitive advantage on business performance. It is suggested for future research generalize the performance of SMEs more broadly, can be done cross-district. Also that SMEs should keep control of organizational behavior with the theory of planned behavior, more attention to innovation business aspects, utilize information technology for knowledge exchange with other SMEs. It is recommended to use the questionnaire with interviews and observation of business activities.